Pantoea agglomerans as a New Etiological Agent of a Bacterial Necrotic Disease of Mango Trees. - Gutiérrez Barranquero, José Antonio; Cazorla-López, Francisco Manuel; Torés, Juan Antonio; De-Vicente-Moreno, Antonio (American Phytopathological Society, 2018)
Bacterial apical necrosis of mango trees, a disease elicited by Pseudomonas syringae pv. syringae, is a primary limiting factor of mango crop production in the Mediterranean region. In this study, a collection of bacterial isolates associated with necrotic symptoms in mango trees similar to those produced by bacterial apical necrosis disease were isolated over five consecutive years in orchards from the Canary Islands. The bacterial isolates were characterized and identified as Pantoea agglomerans. Pathogenicity tests conducted on onion bulbs and mango plants confirmed that P. agglomerans strains isolated from mango trees are a new etiological agent of a bacterial necrotic disease in the Canary Islands. Pathogenicity plasmids of the pPATH family have been previously reported in P. agglomerans. The majority of putatively pathogenic (n = 23) and pathogenic (n = 4) P. agglomerans strains isolated from mango trees harbored four plasmids, one of which was close in size to the 135-kb pPATH pathogenicity plasmid. The analysis of the presence of two major genes in pPATH plasmids (repA and hrpJ) was undertaken in P. agglomerans strains isolated from mango trees. The hrpJ gene was detected in the 140-kb plasmid of pathogenic P. agglomerans strains isolated from mango trees but it showed differences in nucleotide sequences compared with other pathogenic strains. In contrast, the repA gene was not detected in any of the putatively pathogenic and pathogenic P. agglomerans strains isolated from mango trees. Finally, genetic characterization and phylogenetic analysis using the hrpJ gene and the housekeeping genes gyrB and rpoB showed that almost all P. agglomerans strains that were putatively pathogenic and pathogenic on mango trees clustered together, forming a differentiated phylogroup with respect to the other pathogenic P. agglomerans strains described from other hosts.
https://v2.sherpa.ac.uk/id/publication/10350?template=romeo
Keywords: Mangos - Enfermedades y plagas; Pantoea agglomerans; Mango; Bacterias patógenas